Milimeter wave carrier generation using stimulated brillouin scattering in optical fiber [electronic resource] - Aishah Muzni, 1984- (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2010